Augmented Reality Prototype to Introduce Gamelan Based on Web - Ramadiyan, Avriyasendy; Wijayanti, Sari (IPTEK Journal of Proceedings Series, 2014)
Gamelan is a set of musical instruments used to accompany an art show or ceremony that originated from Java, Bali and Lombok. Augmented Reality which was later shortened to AR is a technology that allows a computer to display the virtual objects appropriately in a real object in real time. Interest in the study the gamelan music instruments are still relatively low. Therefore, it takes an effort to introduce a more gamelan creative and innovative. With prototype samples demung, is expected to be an alternative to introducing gamelan to the public. Using the methods of action research and prototyping systems development methods in the design accuracy and speed of the model can be solved by good and with prototype samples demung, is expected to be an alternative to introducing gamelan to the public. Using a programming language javaScript prototype is expected this will be more flexible and accessible to anyone, anytime, anywhere.Conclusions based on the benefits and approval UAT respondents Augmented Reality gamelan, the rating given to a prototype is worth 3,067 and 3.4 which means that the respondents considered if the prototype can be used as a media to introduce gamelan